1992
DOI: 10.1093/nar/20.4.735
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of the cDNA for the catalytic subunit of human DNA polymerase δ

Abstract: The cDNA of human DNA polymerase delta was cloned. The cDNA had a length of 3.5 kb and encoded a protein of 1107 amino acid residues with a calculated molecular mass of 124 kDa. Northern blot analysis showed that the cDNA hybridized to a mRNA of 3.4 kb. Monoclonal and polyclonal antibodies to the C-terminal 20 residues specifically immunoblotted the human pol delta catalytic polypeptide. A multiple sequence alignment was constructed. This showed that human pol delta is closely related to yeast pol delta and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 71 publications
2
53
0
Order By: Relevance
“…After heating at 95°C for 5 min and chilling on ice, products were separated on 6% PAGE in Tris borate-EDTA with 7 M urea. (21). The resequencing of a number of partial cDNA clones that had been generated by PCR amplification of poly(A) ϩ RNA from HepG2 cells using primers HGF3/HR3 and H3/HGR5 (18) revealed that codons for Arg-30 and Tyr-472 were present in some clones and were likely correct, whereas codons for His-119, Asn-173, and Gly-776 were not present in any of our clones.…”
Section: Sds-polyacrylamide Gel Electrophoresis and Proteinmentioning
confidence: 77%
“…After heating at 95°C for 5 min and chilling on ice, products were separated on 6% PAGE in Tris borate-EDTA with 7 M urea. (21). The resequencing of a number of partial cDNA clones that had been generated by PCR amplification of poly(A) ϩ RNA from HepG2 cells using primers HGF3/HR3 and H3/HGR5 (18) revealed that codons for Arg-30 and Tyr-472 were present in some clones and were likely correct, whereas codons for His-119, Asn-173, and Gly-776 were not present in any of our clones.…”
Section: Sds-polyacrylamide Gel Electrophoresis and Proteinmentioning
confidence: 77%
“…Arginine residues at codon 506 of the POLD1 gene are highly conserved from yeast to mammals 21,44 and, therefore, R506H in DLD-1 cells is regarded as impairing the protein function and, consequently, as a dysfunctional mutation. 44 Valine residues at codon 312 are also conserved between mouse and human, although differing in yeast.…”
Section: Resultsmentioning
confidence: 99%
“…As pol epsilon possesses a relatively high processivity, it is now widely accepted that in eukaryotic cells pol delta and epsilon are responsible for the lagging-and leading-strand synthesis, respectively, 19 although pol epsilon has been demonstrated not to be essential in yeast. 20 The catalytic subunits of pol delta and epsilon, for example, p125 [21][22][23] and p261 24,25 in mammals, include the 3¢ exonuclease, that is, proofreading, domains. Indeed, in the yeast mutants in which pol delta or epsilon proofreading is selectively inactivated, the mutations rates are 10-100 times higher than the wild-type strains.…”
Section: Introductionmentioning
confidence: 99%
“…Human Pol d4 is a heterotetramer of p125, p50, p68, and p12 subunits, like yPold4 in S. pombe. The catalytic core region of human p125 was found to share >60% similarities with those of S. cerevisiae and S. pombe Pol d, indicating a strong evolutionary conservation Yang et al, 1992]. However, p68 and p12 are poorly conserved with their yeast counterparts .…”
Section: Introductionmentioning
confidence: 99%
“…A second form of ''Pol d'' with a larger catalytic subunit was discovered and is now known as Pol e [Syvaoja et al, 1990;Pospiech and Syvaoja, 2003;Pursell and Kunkel, 2008]. Molecular cloning of p125 showed that the catalytic core was highly conserved in evolution from T4 bacteriophage to human Hao et al, 1992;Yang et al, 1992], and Pol d is now classified as a member of the B family polymerases. Closely allied with the early history of Pol d are studies of the eukaryotic DNA-sliding clamp, proliferating cell nuclear antigen (PCNA; [Kuriyan and O'Donnell, 1993;Moldovan et al, 2010]), which was discovered as a processivity factor that stimulated Pol d activity [Prelich et al, 1987].…”
Section: Introductionmentioning
confidence: 99%